2020
DOI: 10.1001/jamanetworkopen.2020.1617
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Effectiveness and Safety of Osimertinib for Patients With Intracranial Metastatic Disease

Abstract: IMPORTANCE Intracranial metastatic disease (IMD) is a serious and life-altering complication for many patients with cancer. Targeted therapy may address the limitations of current treatments as an additional agent to achieve intracranial disease control in some patients with IMD. Given the paucity of evidence regarding effectiveness, current guidelines have not made recommendations on the use of targeted therapy. Osimertinib mesylate is a mutant epidermal growth factor receptor (EGFR) inhibitor that can penetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…EGFR amplification was observed in BM samples but not in lung lesions, suggesting that those patients were resistant to EGFR TKI. Osimertinib a third generation EGFR-TKI has demonstrated excellent CNS response of 91% in patients with EGFR-mutant NSCLC in both first and second-line setting [ 17 ]. For example, in the phase III FLAURA trial, the CNS efficacy of osimertinib was demonstrated in the first-line setting with fewer patients in the osimertinib arm developing new brain lesions compared with the control arm (12% versus 30%) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…EGFR amplification was observed in BM samples but not in lung lesions, suggesting that those patients were resistant to EGFR TKI. Osimertinib a third generation EGFR-TKI has demonstrated excellent CNS response of 91% in patients with EGFR-mutant NSCLC in both first and second-line setting [ 17 ]. For example, in the phase III FLAURA trial, the CNS efficacy of osimertinib was demonstrated in the first-line setting with fewer patients in the osimertinib arm developing new brain lesions compared with the control arm (12% versus 30%) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Osimertinib, a third-generation EGFR TKI, has high CNS penetration [47] (Figure 1). In a retrospective study of NSCLC BM patients, Xie et al compared the outcomes of patients treated with RT and osimertinib versus osimertinib alone [48].…”
Section: Epidermal Growth Factor Receptor (Egfr)-tkismentioning
confidence: 99%
“…One of the factors responsible for limited long-term survival rates is the development of central nervous system (CNS) metastases, which typically are located in the brain or meninges. Their multidisciplinary treatment involves different radiotherapy modalities, surgical resection, and systemic therapy [2][3][4][5][6][7][8]. Defined subtypes of NSCLC, e.g., those with epidermal growth factor receptor (EGFR) mutations or anaplastic lymphoma kinase (ALK) translocations, may respond to targeted agents; however, wild-type NSCLC (negative EGFR, ALK, and other common alterations) is the prevailing tumor type in the authors' geographical region [9].…”
Section: Introductionmentioning
confidence: 99%